2019
DOI: 10.1101/778233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The 5’-NAD cap of RNAIII modulates toxin production in Staphylococcus aureus isolates

Abstract: 10 Nicotinamide adenosine dinucleotide (NAD) has been found to be covalently attached to the 5'-11ends of specific RNAs in many different organisms, but the physiological consequences of this 12 modification are largely unknown. Here we report the occurrence of several NAD-RNAs in the 13 opportunistic human pathogen Staphylococcus aureus. Most prominently, RNAIII, a central 14 quorum-sensing regulator of this bacterium's physiology, was found to be 5'-NAD-capped to a 15 significant extent. NAD incorporation ef… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…RNAs in prokaryotes were once thought to lack a cap and have only a 5′-triphosphorylated end from the initiation nucleotide (5). However, it has been recently reported that some RNAs in bacteria contain a nicotinamide adenine dinucleotide (NAD + ) moiety at their 5′ end (6)(7)(8)(9)(10). Later, eukaryotic organisms, including yeast, mammalian cells, and Arabidopsis plants, were also found to produce NAD-capped RNAs (NAD-RNAs) (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…RNAs in prokaryotes were once thought to lack a cap and have only a 5′-triphosphorylated end from the initiation nucleotide (5). However, it has been recently reported that some RNAs in bacteria contain a nicotinamide adenine dinucleotide (NAD + ) moiety at their 5′ end (6)(7)(8)(9)(10). Later, eukaryotic organisms, including yeast, mammalian cells, and Arabidopsis plants, were also found to produce NAD-capped RNAs (NAD-RNAs) (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…So far, only the method for NAD-RNA sequencing had been developed. 4) Thanks to that, we know that NAD-RNA is present in all types of cells including bacteria, 4,5) humans, 6) plants 7) and Archaea 8) . Nevertheless, the role of the NAD-RNA cap is still unclear.…”
Section: Wissenschaft + Forschungmentioning
confidence: 99%
“…The cap is hydrolyzed by various decapping enzymes (Belasco, 2010), thereby triggering RNA degradation. Recently, another type of 5'-cap structure was discovered, both in prokaryotes Frindert et al, 2018;Morales-Filloy et al, 2020) and eukaryotes (Jiao et al, 2017;Walters et al, 2017;Wang et al, 2019;Zhang et al, 2019), that is derived from the ubiquitous redox coenzyme NAD. While in human and plant cells a diverse landscape of NAD-RNAs was found, only 37 RNA species and low abundance were reported in budding yeast (Walters et al, 2017), questioning the biological significance of NAD capping in this organism.…”
Section: Introductionmentioning
confidence: 99%